Efecto del déficit hídrico en el comportamiento en postcosecha en tomate riñón (Solanum Lycopersicum) CAMPUS CEASA 2022. - Sánchez Caiza, Juan Fernando (2022)
Commercial tomato cultivation requires a lot of water throughout its production cycle, being susceptible to water stress without adequate irrigation frequency. In the present investigation, the effect of water deficit on tomato postharvest behavior was evaluated by comparing four irrigation frequencies (daily and, passing 1; 2; and 3 days) and three irrigation suspensions (without deficit; 3 days, and 5 days). before harvest) in two color indices (Tornando and Rosa) and its effect on chemical and organoleptic properties. Field work was carried out in a greenhouse in the Guitig Bajo sector in the city of Machachi, and the properties were evaluated in the laboratory in a total of 720 tomatoes at 2, 9 and 14 days after harvest. Additionally, the number of tomatoes that presented some disease or physiopathy was quantified. The results showed that the "daily" irrigation frequency generated a greater weight loss at all evaluation times (2.68gr [2 days]; 6.79 [9 days]; 9.47 [14 days]). The irrigation frequency "after 2 days" generated greater firmness (2.68Nw/Kg [2 days]; 3.23 [14 days]), the frequency "after 1 day" was for pH (4.28 [2 days]; 4.27 [9 days]; 4.42 [14 days]), while the irrigation frequency "after 2 days" was for soluble solids except after 2 days, and 14 days for total ashes. The irrigation suspension "without water deficit" generated a greater weight loss between 9 to 14 days (6.54 gr) and between 2 to 14 days (8.83 gr), and a higher pH at all evaluation times ( 4.25 [2 days], 4.23 [9 days], 4.41 [14 days]). The suspension "5 days before harvest" caused greater tomato firmness at 2 days (3.34 Nw/Kg) and 9 days (3.18 Nw/Kg), and a greater amount of soluble solids at 9 ( 4.96 brix) and 14 days (4.20 brix), while the suspension "3 days before harvest" generated greater firmness at 2 (3.34 Nw/Kg) and 9 days (3.18 Nw/ Kg), and the suspension "5 days before harvest" at 14 days (2.98 Nw/Kg) after harvest. For total ashes, no significant effect of any of the variables was evidenced. It was concluded that the best harvest index was the color "Tornando" in order to obtain a tomato with greater firmness, higher pH, and greater amount of soluble solids. The presence of diseases was low with an average of 1 for every 10 tomatoes evaluated. This study recommends an adequate irrigation management program for tomato, suggesting daily irrigation for 10 minutes, with suspension of irrigation every 3 days if less weight loss is desired, or every 5 days if greater firmness is desired, depending on the conditions, farmer and consumer needs.